Birth of a science centre. Italian phenomenology (Italian original version) - Paola Rodari (JCOM: Journal of Science Communication, 2006)
In May 2004 the Balì Museum, Planetarium and interactive science museum, was opened to the public in Italy: 35 hands-on exhibits designed according to the interactive tradition of the Exploratorium in San Francisco, an astronomic observatory for educational activities, a Planetarium with 70 places. With a total investment of about three million euros, about two thirds of which were spent on restructuring the splendid eighteenth-century villa in which it is housed, the undertaking may be considered a small one in comparison with other European science centres. Three million euros: perhaps enough to cover the cost of only the splendid circular access ramp to the brand-new Cosmocaixa in Barcelona, an investment of one hundred million euros. But the interesting aspect of the story of the Balì Museum (but also of other Italian stories, as we shall see) lies in the fact that this lively and advanced science centre stands in the bucolic region of the Marches, next to a small town of only 800 inhabitants (Saltara, in the Province of Pesaro and Urbino), in a municipal territory that has a total of 5000. Whereas in Italy the projects for science centres comparable with the Catalan one, for example projects for Rome and Turin, never get off the ground, smaller ones are opening in small and medium-sized towns: why is this? And what does the unusual location of the centres entail for science communication in Italy? This Focus does not claim to tell the whole truth about Italian interactive museums, but it does offer some phenomenological cues to open a debate on the cultural, economic and political premises that favour their lives.